Identification of regions critical for the integrity of the TSC1-TSC2-TBC1D7 complex. - Arthur Jorge Santiago Lima; Marianne Hoogeveen-Westerveld; Akio Nakashima; Anneke Maat-Kievit; Ans van den Ouweland; Dicky Halley; Ushio Kikkawa; Mark Nellist (PLoS ONE, 2014)
The TSC1-TSC2-TBC1D7 complex is an important negative regulator of the mechanistic target of rapamycin complex 1 that controls cell growth in response to environmental cues. Inactivating TSC1 and TSC2 mutations cause tuberous sclerosis complex (TSC), an autosomal dominant disorder characterised by the occurrence of benign tumours in various organs and tissues, notably the brain, skin and kidneys. TBC1D7 mutations have not been reported in TSC patients but homozygous inactivation of TBC1D7 causes megaencephaly and intellectual disability. Here, using an exon-specific deletion strategy, we demonstrate that some regions of TSC1 are not necessary for the core function of the TSC1-TSC2 complex. Furthermore, we show that the TBC1D7 binding site is encoded by TSC1 exon 22 and identify amino acid residues involved in the TSC1-TBC1D7 interaction.